Local effects in the analysis of structures - Ladeveze, Pierre, 1945- (Studies in applied mechanics, 1985)
The question of inclusion of local effects in the analysis of structures is currently one of prime importance for engineering design. The classical computational approaches are not readily adapted to take local effects into account and appropriate treatments are therefore necessary. Providing an introduction to and survey of the specific computational methods, this book contains 16 papers, most of which were presented at the EUROMECH Colloquium `Inclusion of Local Effects in the Analysis of Structures', held in France in 1984. The book begins with the various theories which allow the separat.